Isothermal microcalorimetry (IMC) to determine antagonistic effects of Trichoderma asperellum and Bacillus amyloliquefaciens against Scopulariopsis sp. - Uribe, L.; Beltrán Acosta, C.; Toloza Moreno, D.; Suárez, M.; López, M.; Rodríguez, T.; Braissant, O.; Bravo, D. (Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2025)
Scopulariopsis fungi genus has 112 recognized species in Index-Fungorum (http://www.indexfungorum.org/Names/Names.asp). Some species are classified as a human opportunistic FFHP (Jagielski et al., 2016). These species are able to produces toxins or carry allergens, which cause health hazards (Woudenberg et al. 2017). In environmental sciences, a new species of S. gossypii was categorized an opportunistic pathogen causing leaf interveinal chlorosis and vascular browning of cotton plants (Li et al. 2017). It has been isolated from a wide variety of substrates, containing both hyaline and somewhat pigmented filamentous fungi that normally are saprotrophs (Sandoval-Denis et al. 2013). Control of the pathogen Scopulariopsis sp. is conducted by chemical antifungals such as sertaconazole, terbinafine and tioconazole (Carrillo-Muñoz et al. 2004), however with high costs and low results in environmental conditions. Despite the presence of different Scopulariopsis sp. species facilitating vascular wilt, biological control as a strategy against this fungus is not common. A non-conventional technique that has been used recently in biological control of microorganisms within agro-ecosystems is isothermal microcalorimetry (IMC) (Yao et al. 2007). It is a sensitive method for real-time monitoring and dynamic analysis of chemical, physical and biological processes (Braissant et al. 2010) used to measure metabolic activity of relevant environmental microorganisms (Bravo et al., 2011). This research aims to determine the use of IMC to assess the antagonic activity of Trichoderma. asperellum (Th034 and Th406), the metabolic interaction between Th034, Th406, and Bacillus amyloliquefaciens (Bs006) against Scopulariopsis sp. (Sc002) either independently or in consortium. Using the kinetical parameter data obtained after fitting the Richards equation of growth, an Anova test was performed to compare the variance between the antagonic populations and the target population of Scopulariopsis sp. Using the maximum heat values (Qmax in J.h-1), the fractional inhibitory concentration index of Scopulariopsis sp. (FIC) was calculated as shown in a previous study (Fälcao et al., 2014). The FIC index was above the treshold for antagonic activity using T. asperellum Th406. Using a standardized medium developed in this study, this research demonstrates that Scopulariopsis sp., is inhibited due the metabolic activity of T. asperellum (Th406) measured by IMC with a FIC of 4.88. Thus, the strain Th406 is suggested as a promising microbial agent against Scopulariopsis sp. Sc002.